Peculiarities of the radiation formation in dispersed microencapsulated nuclear fuel; Nuclear Energy and Technology; Vol. 5, № 1 - Bedenko S. V. Sergey Vladimirovich; Knyshev V. V. Vladimir Vladimirovich; Kuznetsova M. E. Mariya Evgenjevna; Lutsik I. O. Igor Olegovich; Shamanin I. V. Igor Vladimirovich (2019, 2019)
Заглавие с экрана